Oxidation behavior of SiC nanowires: A nanowire radius‐dependent growth of oxide scale thickness. Issue 1 (8th September 2022) - Qu, Ruina; Lu, De; Su, Lei; Niu, Min; Peng, Kang; Gao, Hongfei; Guo, Pengfei; Xu, Liang; Zhuang, Lei; Wang, Hongjie
Abstract: SiC nanowires (SiC NWs) possess both high thermal stability of SiC ceramic and one‐dimensional nanoscale features, which makes them highly attractive as reinforcements in ceramics or building units in resilient ceramic nanowires aerogels (NWAs) as well as blocks for electronic nanodevices. Understanding the oxidation behavior of SiC NWs at high temperatures is essential for their practical applications. Herein, we investigated the oxidation behavior of SiC NWs at 900–1200°C in air. Two oxidation stages were found, including an initial stage controlled by the reaction between oxygen and SiC at the SiO2 /SiC interface and a subsequent oxygen diffusion–dependent stage. The oxide scale thickness was strongly influenced by the radius of the SiC NWs. With the increase of the NW radius from 40 to 120 nm, the oxidation activation energy of the oxidation process increases from 84.05 to 98.32 kJ/mol. The thermal insulation performances of SiC NWA, which is composed of SiC NWs, have been improved after oxidation. The evolution of the thermal insulation performance of SiC NWA during oxidation is consistent with the trends of the growth of the amorphous oxide layer, which indicates that exploring the oxidation kinetics is of great significance in understanding the high‐temperature behavior of SiC NW‐based materials. The present work provides insight into exploring the size effects on oxidation of SiC NWs, which may be helpful to further understanding the high‐temperature applications of SiC NWA.